SMEs in Foreign Trade of the Czech Republic - Richter, Stanislav; Halík, Jaroslav, 1961-; Štěrbová, Ludmila, 1957-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2012)
This diploma thesis deals with the question of export support for small and medium enterprises in the context of international trade of the Czech Republic. It presents a comprehensive study of the development of foreign trade of the Czech Republic since 1993 to the present, focusing especially on the role of small and medium-sized enterprises and their importance for the whole economy. Fruther it maps the availability of both state and private export support services which are consequently compared with actual needs, identified through own research among small and medium-sized enterprises. On these basis possible modifications leading to more efficient and transparent system are recommended with ambitions to improve the export performance of small and medium-sized enterprises.
Vedoucí práce: Jaroslav Halík
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses